A Study on the Work-Life Conflict of the Malaysian Working Women in Sales and Service Industry - Erschad, Ahamed (2014)
As per the statistics of Malaysian population, it seems that the women labor force have been drastically increasing in many industries especially in sales and service. Even though this increase is highly needed for the citizen but there are few questions that arise regarding the work life conflict. How Malaysian women balance their life between the work domain and life domain? Thus to identify these issues, the researcher has done a research to find out those factor/variables that influence them in the work life conflict. This particular study is being carried out in 2 main places of Malaysia where there are large number sales and service industries i.e. Melaka and Kuala Lumpur. The data are collected by distributing the questionnaires to the women respondents in sales and service industry. Than these data were analyzed by descriptive, reliability and factor analysis. Based on findings and data analysis the recommendation and conclusion are provided accordingly.